Oncovascular Surgery: Essential Roles of Vascular Surgeons in Cancer Surgery - Han, Ahram (Vasc Specialist Int, 2019)
For the modern practice of cancer surgery, the concept of oncovascular surgery (OVS), defined as cancer resection with concurrent ligation or reconstruction of a major vascular structure, can be very important. OVS for advanced cancers requires specialized procedures performed by a specialized multidisciplinary team. Roles of oncovascular surgeons are summarized as: a primary surgeon in vesselorigin tumors, a rescue surgeon treating complications during cancer surgery, and a consultant surgeon as a multidisciplinary team for cancer surgery. Vascular surgeons must show leadership in cancer surgery in cases of complex advanced diseases, such as angiosarcoma, leiomyosarcoma, intravenous leiomyomatosis, retroperitoneal soft tissue sarcoma, iatrogenic injury of the major vessels during cancer surgery, pancreatic cancer with vascular invasion, extremity soft tissue sarcoma, melanoma and others.